2022
DOI: 10.1155/2022/1182866
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Extract of Leaves of Mistletoe as a Benalu Duku: Clinical Chemical Value Associated with Histopathology, Liver, Kidneys, and Lethal Dose Determinate

Abstract: The active compounds from the leaves of Dendrophthoe pentandra L. Miq., also known as, Benalu Duku (in Indonesia), are known to contain progesterone-like compounds (PLCs). This study aims to determine the effect of giving a single dose of PLCs on liver and kidney function in rats and the dose limit that causes the death of experimental animals. The PLCs were analyzed for chemical and physical characterization and compared to a pure standard of progesterone using HPLC, IR spectrometry, thermogravimetry, and NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The technique was also carried out on a standard compound (quercetin). 6,27,28 Proton nuclear magnetic resonance ( 1 H NMR) and carbon nuclear magnetic resonance ( 13 C NMR) were performed using a JEOL NMR (JNM ECS-400, 400 MHz). Analysis of NMR protons and NMR carbons begins by dissolving analytes (QLCs) using the solvent-deuterated methanol (CD3OD), as well as the comparison compound (quercetin).…”
Section: Separation Of Quercetin-like Compounds Of Benalu Dukumentioning
confidence: 99%
See 1 more Smart Citation
“…The technique was also carried out on a standard compound (quercetin). 6,27,28 Proton nuclear magnetic resonance ( 1 H NMR) and carbon nuclear magnetic resonance ( 13 C NMR) were performed using a JEOL NMR (JNM ECS-400, 400 MHz). Analysis of NMR protons and NMR carbons begins by dissolving analytes (QLCs) using the solvent-deuterated methanol (CD3OD), as well as the comparison compound (quercetin).…”
Section: Separation Of Quercetin-like Compounds Of Benalu Dukumentioning
confidence: 99%
“…4 In terms of its antiviral properties, there are generally three main places where functional groups may cause these effects, namely complex aromatic structures, electron attractor groups, and quercetin analogs. 5,6 That concept can be explained using theory based on quantification structure-activity relationship versus virus agents. As an anti-virus, it is suitable for killing viruses that live and develop in host eukaryote cells that have the property of being able to regrow themselves against eukaryote cells that have been damaged such as intestinal cells, skin epithelial cells, epithelial cells of the reproductive tract.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that the percolation of mistletoe leaves from Dendrophthoe pentandra (L.) Miq, or benalu duku as it is known in Indonesia, is known to potentially have anticancer, antivirus, and antidiabetic activity (Lazuardi et al. 2022 ; Kong et al. 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The multilevel maceration technique produces compounds rich in polyphenols and a small amount of condensed and hydrolyzable tannins (Lazuardi et al. 2022 ). This is possible considering that the plant is known to contain quercetin-like compounds (QLCs) as secondary metabolites or analytes that have a protective role on the surface of eukaryote cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation